Pengaruh Self-Efficacy dan Lingkungan Kerja terhadap Kinerja Karyawan di Quest Hotel Kuta Bali - I Kadek Riski Adi Saputra; Ni Wayan Mekarini; Endrayani Endrayani (Lembaga Pengembangan Kinerja Dosen, 2026)
This study is motivated by the importance of employee performance as a strategic factor in maintaining service quality in the hospitality industry, especially city hotels such as Quest Hotel Kuta, which face the challenges of performance variation and guest complaints related to service. This research is based on Bandura's self-efficacy theory, Sedarmayanti's work environment concept, and Mangkunegara's employee performance theory, which are integrated into a conceptual framework to examine the influence of self-efficacy and work environment on employee performance. The approach used is quantitative with a causal associative design, using a population of 43 employees at Quest Hotel Kuta who were taken through a total sampling technique. Using SPSS, instrument testing, classical assumption testing, multiple linear regression, correlation, t-test, F-test, and coefficient of determination were carried out. Primary data were collected through a Likert scale questionnaire and supplemented by observations, interviews, and documentation studies. The research shows that the work environment and employee self-efficacy have a positive and substantial influence on performance, and these two factors interact strongly to influence the level of employee determination. Efforts to improve staff performance at Quest Hotel Kuta are centered on increasing self-efficacy and improving the work environment.